MANAGEMENT OF CHARACTER EDUCATION IN KINDERGARTEN - Nanik Lestari (JIV-Jurnal Ilmiah Visi, 2022)
The purpose of this study was to determine the application of character education management in Kindergarten 2 Sukarame Bandar Lampung. Data collection techniques using observation, interviews and document studies. Data analysis uses data reduction, data presentation and conclusions. The results showed that the management of character education was developed through (a) the planning stage, the teachers prepare themes, learning methods, determine the types and learning plans to be implemented, socialize the program to parents and arrange various activities arranged in the educational calendar, and prepare Promissory notes. , Rkm and Rpph (b) Implementation stage, at this stage in the division of tasks, responsibilities and authority of character education listed in the organizational structure (c) Supervision Stage, the first supervision is to lead, then supervision is to direct (d) Evaluation stage, At this stage the teacher informs parents in written form or is directly related to the development of the child's character. Character education today is an ongoing discussion in the implementation of educational programs. The curriculum which consists of various educational institutions inserts character as a lesson material that is instilled in students, more than that in Islamic educational institutions, character education in organizations and in student activities.